Polycyclic polyprenylated acylphloroglucinol derivatives with neuroprotective effects from Hypericum monogynum. Issue 1 (2nd January 2021) - Zeng, Yan-Rong; Li, Ya-Na; Lou, Hua-Yong; Jian, Jun-You; Gu, Wei; Huang, Lie-Jun; Du, Guan-Hua; Yuan, Chun-Mao; Hao, Xiao-Jiang
Abstract: A new polycyclic polyprenylated acylphloroglucinol (PPAP), hypermonin C (1 ), along with nine known PPAPs (2 –10 ) were obtained from the leaves and twigs of Hypericum monogynum . The structures of the isolates were determined on the basis of extensive spectroscopic analysis. The neuroprotective effects of the isolates against several chemical-induced injuries in SH-SY5Y and PC12 cells were assessed, and most of the compounds exhibited significant protective effects at 10 μg/ml. Especially, three compounds (1, 3, and 7 ) showed excellent neuroprotective activity with a cell viability of 92.4% ∼ 95.8% in KCl-induced SH-SY5Y cell injury. Their preliminary structure-activity relationship was also discussed and the configuration of substituent in furohyperforin may be critical for the neuroprotective activity of PPAP derivatives. Abstract :